Physical and chemical properties of a Ga-doped ZnO crystal - Stashans, A. (2011)
First-principles calculations based on density functional theory and strengthened by Hartree-Fock computations have been performed to study a Ga-doped wurtzite-type ZnO crystal. The large 108-atom supercell used throughout this work allows one to model a single point defect within the periodic supercell model. Thus, the Ga impurity produced purely local effects on the properties of the material. The electronic band structure was obtained for both pure and impurity-doped materials. The occurrence of free electrons in the conduction band was observed after the incorporation of Ga, implying the Ga dopant s contribution to n-type electrical conductivity in the ZnO crystal, in agreement with known experimental data. An analysis of the charges on atoms and obtained atomic displacements in the region surrounding the defect showed that there is some alteration in the chemical bonding because of the presence of Ga atoms. In particular, the ionic bonding is strengthened in the defect s neighbourhood. © 2011 The Royal Swedish Academy of Sciences.